2019
DOI: 10.1002/pc.25227
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on interlayer phase morphology evolution of “Ex‐Situ” toughened composite laminate

Abstract: The numerical simulation on the interlayer phase morphology evolution of "Ex-Situ" toughened laminate was performed in this study. Specifically, the diffusion process of thermoset (TS) resin into thermoplastic (TP) resin was modeled incorporating the negative effect of resin curing reactions. The dynamic process of polymerization-induced phase separation in TP/TS blends was predicted by the modified Cahn-Hilliard equation, in which the concentration-dependent mobility was used to describe dynamic asymmetry bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As previously reported, the two-phase structure in the TP/TS blends system may be formed via PIPS, which can improve the toughness of thermoset matrix significantly. [15,18] The studies showed that the phase morphology of TP/TS mixtures had a close relationship with the initial TP concentration, [19][20][21] molecular structure, [22][23] and the curing temperature. [24][25] With the TP content increased, the phase morphology of mixtures transformed from the islands-sea structure to bicontinuous structure, and finally in the form of phaseinverted structure.…”
Section: Cell Structures and Phase Morphologies Of Fre-foamsmentioning
confidence: 99%
“…As previously reported, the two-phase structure in the TP/TS blends system may be formed via PIPS, which can improve the toughness of thermoset matrix significantly. [15,18] The studies showed that the phase morphology of TP/TS mixtures had a close relationship with the initial TP concentration, [19][20][21] molecular structure, [22][23] and the curing temperature. [24][25] With the TP content increased, the phase morphology of mixtures transformed from the islands-sea structure to bicontinuous structure, and finally in the form of phaseinverted structure.…”
Section: Cell Structures and Phase Morphologies Of Fre-foamsmentioning
confidence: 99%
“…A typical viscosity profile of dissolved thermoplastic/epoxy blends was shown in Figure 2(b). [29][30][31] The initially complex viscosity of the dissolved blends decreases abruptly and then levels off with the increase in temperature. As the temperature further increased, curing reaction of the epoxy resin accrued.…”
Section: Rheological Behaviour Of the Undissolved Pek/ Dgeba/m-dicy Bmentioning
confidence: 99%
“…Based on the Flory-Huggins free energy of mixing, Zhu et al (2016) proposed an expression for PMB free energy with a hypothetical dilution process as a simplification. Some other researchers recently adopted this expression and investigated the phase behaviour of polymer composites as well as PE-and SBS-modified bitumen (Ding, Yao, Gong, Chen, & Ren, 2019;Liang, Xin, Fan, Wang, Jiang, et al, 2019;Liang, Xin, Fan, Wang, & Sun, 2019). This dilution simplification can be interpreted by solubility bodies.…”
Section: Proposed Free Energy For Pmb: Hypothetical Dilutionmentioning
confidence: 99%